A familiar compound ghost : allusion and the uncanny - Brown, Sarah Annes (Manchester University Press, 2017)
A Familiar Compound Ghost explores the relationship between allusion and the uncanny in literature. An unexpected echo or quotation in a new text can be compared to the sudden appearance of a ghost or mysterious double, the reanimation of a corpse, or the discovery of an ancient ruin hidden in a modern city. In this scholarly and suggestive study, Brown identifies moments where this affinity between allusion and the uncanny is used by writers to generate a particular textual charge, where uncanny elements are used to flag patterns of allusion and to point to the haunting presence of an earlier work. A Familiar Compound Ghost traces the subtle patterns of connection between texts centuries, even millennia apart, from Greek tragedy and Latin epic, through the plays of Shakespeare and the Victorian novel, to contemporary film, fiction and poetry. Each chapter takes a different uncanny motif as its focus: doubles, ruins, reanimation, ghosts and journeys to the underworld.
Contents List 1. Introduction 2. Uncanny doubles: part one 3. Uncanny doubles: part two 4. Ruins 5. Reanimation: Orpheus and Pygmalion 6. The ghost in Hamlet 7. A familiar compound ghost: katabasis and The Tempest 8. Afterword: 'You'd think she would remember all this from the first time.' Bibliography.
Keywords: Allusions in literature.; Uncanny, The (Psychoanalysis), in literature.; Allusions dans la littérature.; Inquiétante étrangeté (Psychanalyse) dans la littérature.; Literature.; Literature / History & Criticism.; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh.; LITERARY CRITICISM / Horror & Supernatural.; Uncanny, The (Psychoanalysis), in literature; Allusions in literature; Ireland -- Literature -- history & criticism -- United Kingdom, Great Britain.; Greek tragedy.; Latin epic.; Shakespeare.; Victorian novel.; allusion.; fiction.; film.; ghosts.; poetry.; uncanny.; Electronic books